The Number and Types of Bacteria in the Bali Cattle’s Vagina during Estrus and Pregnant - Ketut Tono PG; Putu Henrywaesa Sudipa; I Gusti Ketut Suarjana (Institute for Research and Community Service, Udayana University, 2020)
Bali cattle have very good potential for meat and calf supply, because they have good adaptability with good quality reproductive properties. However, good reproductive nature is threatened by diseases caused by bacteria. This study aims to determine the number and types of bacteria in the vagina of Bali cattle that are estrus and pregnant. Sample using vaginal swabs from 30 cows. The sample consisted of 10 swabs from non-estrus and not pregnant (control / normal) cattle, 10 swabs from estrus cows, and 10 swabs from pregnant cows. After the swab is carried out using a cotton bud, the results of the swab are stored in Stuart transport media. Samples planted in blood media to be identified and the number of colonies counted, then followed by Gram staining and biochemical tests then the results were presented descriptively. The result is the highest number of estrous cow colonies (1034 colonies), compared to non-estrous and non-pregnant cows (407 colonies) and pregnant (376 colonies). This type of bacteria is dominated by Klebsiella sp. (42.85%), Eschericia coli (28.7%), Streptococcus sp. (14.28%) and Bacillus sp. (14.28%).